ERETMOCERUS SERIUS SILV AS A PARASITE OF THE CITRUS BLACKFLY IN MEXICO - SHAW, JG (Hospital Enfermedades Nutrición, CD MEXICO, DF, MEX, 1913)
The symptoms, life history and control of each of the more common diseases of corn in Mexico are described The most important ear rot is caused by Fusarium moniliforme The ear rots caused by Diplodia zeae and Nigrospora oryzae cause considerable losses
J ECON ENTOMOL
Keywords: ERETMOCERUS SERIUS SILV, PARASITE, CITRUS BLACKFLY, MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA DE INSECTOS; ENTOMOLOGIA GENERAL